Religion, Law and Security in Africa - Green, M Christian (Law and Religion in Africa Series, 2018)
Security is a key topic of our time. But how do we understand it? Do law and religion take different views of it? In this fifth volume in the Law and Religion in Africa series, radicalisation, terrorism, blasphemy, hate speech, religious freedom and just war theories rub shoulders with issues of witchcraft, female genital mutilation circumcision, child marriage, displaced communities and additional issues besides. This unique collection of topics is both challenging and inspiring, providing illumination in troubled times, and forming a sound foundation for future scholarship.